My Name is Hasmah - Siti Hasmah Mohd. Ali Tun 1926- (Grup Buku Karangkraf Sdn. Bhd., 2016)
As one of our first female Malay doctors, Tun Dr Siti Hasmah Mohd Ali belonged to the generation of Malayans who built an independent nation out of a legacy of colonialism and war. She left government service when her husband Tun Dr Mahathir Mohamad reached the top of the political hierarchy, but for the next 22 years she was more than the wife of Malaysia's longest-serving Prime Minister. On the international and local stages she remained a staunch advocate for public health and developmental issues, always engaging the rakyat with her signature grace and humour. My Name is Hasmah is her account of her upbringing, career in medicine and adventures (and occasional misadventures) as she travelled the world by her husband's side. This is a story of a woman who juggled multiple roles-doctor, advocate, daughter, sister, wife, mother-as she navigated a life marked by extraordinary circumstances